2019
DOI: 10.21098/jimf.v4i2.1001
|View full text |Cite
|
Sign up to set email alerts
|

Monetary Transmission Mechanism Under Dual Financial System in Indonesia: Credit-Financing Channel

Abstract: The presence of Islamic and conventional banking in the dual financial system of Indonesia equally hold the role as financial intermediator which theoretically banks collect fund from the debitors to be distributed to creditors. However, along with the changing of time there has been a development in the financial industry, when financial deregulation occurs, where the role of providing credit is not only owned by the banks but also other financial institutions. As the result, banks are no longer considered as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 15 publications
3
13
0
Order By: Relevance
“…This suggests that Islamic banks have not been proven to function as transmitters of monetary policy. This is in line with with Fikri (2018), who demonstrated that Islamic banks are not efficient transmitters, unlike their conventional counterparts. Rafay and Farid (2019) investigated the role of Islamic banks in monetary transmission in Pakistan.…”
Section: Previous Studiessupporting
confidence: 91%
See 2 more Smart Citations
“…This suggests that Islamic banks have not been proven to function as transmitters of monetary policy. This is in line with with Fikri (2018), who demonstrated that Islamic banks are not efficient transmitters, unlike their conventional counterparts. Rafay and Farid (2019) investigated the role of Islamic banks in monetary transmission in Pakistan.…”
Section: Previous Studiessupporting
confidence: 91%
“…This paper aims to fill the gap by focusing solely on the role of Islamic banks in Indonesia in the monetary transmission process. It therefore differs from the studies of Ascarya (2012Ascarya ( , 2014, Herianingrum and Syapriatama (2016), Setiawan and Karsinah (2016), Widodo (2017) and Fikri (2018), which analyzed both conventional and Islamic bank samples. Zulkhibri and Sukmana (2017) employed panel regression analysis, while this paper uses time-series econometrics, i.e Autoregressive Distributed Lag (ARDL), with additional analysis using Granger Causality.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Also, there are two classes of monetary policy, namely expansionary monetary policy to increase the money supply and contractive monetary policy to reduce the money supply. The central bank itself issued this monetary policy through three instruments, namely Open Market Operations (OMO), discount policy and legal reserve requirement (LRR) (Fikri, 2019).…”
Section: Analysis Of Indonesian and Malaysian Monetary Policy Conceptsmentioning
confidence: 99%
“…Other studies that examine monetary policy in Indonesia and Malaysia, including conducted by (Wibowo, 2014) that the benchmark interest rate in setting inflation policy targets in Indonesia is slower when compared to the Singapore and Malaysia benchmark interest rates. Furthermore, research conducted by (Fikri, 2019) the results explain that credit financing is a relevant factor in influencing monetary policy in Indonesia which uses a dual monetary policy system; (Ahmad & Ismail, 2019) hat gross domestic product can be used as an indicator of monetary taxation; (Chaidir, 2019) explained that the exchange rate is the factor that most influences the inflation rate so that and impacts on monetary policy.…”
Section: Introductionmentioning
confidence: 99%